2022
DOI: 10.1001/jamanetworkopen.2022.8794
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Health Care Preferences With Discrete Choice Experiments

Abstract: End-of-life care often includes a constellation of supportive care options marred by conflicting concerns among patients, their families, and health care professionals. Leng et al 1 performed a discrete choice experiment to estimate end-of-life care preferences among terminally ill patients with cancer in China. Although they cited prior studies that have evaluated the end-of-life care preferences of patients in other countries, the authors remarked that China remains an outlier in that it lacks shared decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Ultimately, ACBC analysis provides an efficient method to quantify the RI of factors that vary among reconstruction options. Eliciting individual-level preferences for surgical care can provide a framework for a decision aid that provides objective educational information to patients about their treatment decisions and better aligns patient expectations with the reality of their surgical outcome …”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, ACBC analysis provides an efficient method to quantify the RI of factors that vary among reconstruction options. Eliciting individual-level preferences for surgical care can provide a framework for a decision aid that provides objective educational information to patients about their treatment decisions and better aligns patient expectations with the reality of their surgical outcome …”
Section: Discussionmentioning
confidence: 99%
“…Stated preference methods enable both elicitations of underlying patient preferences and the elucidation of the underlying tradeoffs inherent in complex medical decision‐making. 21 , 22 , 23 These techniques have previously been used in otolaryngology and thyroid surgery. 17 , 24 , 25 , 26 , 27 , 28 Studies have demonstrated that antithyroid drugs for Graves disease were generally preferred by patients over surgery or radioactive iodine, 29 that significant cosmetic considerations regarding thyroid surgery should be factored into decision‐making, 30 and that risk of needing a subsequent contralateral hemithyroidectomy for those undergoing unilateral procedures is a significant driver of decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…These seeming contradictions in what patients want, and the tensions between concern for disease progression and concern for treatment‐related side effects, suggest that further large‐scale, quantitative work should be undertaken. Stated preference methods enable both elicitations of underlying patient preferences and the elucidation of the underlying tradeoffs inherent in complex medical decision‐making 21‐23 . These techniques have previously been used in otolaryngology and thyroid surgery 17,24‐28 .…”
Section: Discussionmentioning
confidence: 99%
“…It is an effective method for eliciting the stated preferences of participants (41–43) and have been widely used in health research, especially in health policy and health economics studies (43–46). DCEs are used to reflect the real-world decision context than other methods in situations where conducting a trial or observational study is impossible or impractical (21, 42, 43). DCEs have been used to identify and evaluate the determinants of hospital choices for patients in a number of settings (9).…”
Section: Introductionmentioning
confidence: 99%